Notifiche
Cancella tutti

Integrale definito

  

1
156

RIsolvere senza X SOSTITUZIONE.

Autore
2 Risposte



2

4·x/((x + 1)·(x + 3)) = Α/(x + 1) + Β/(x + 3)

(fratti semplici)

4·x/((x + 1)·(x + 3)) = (x·(Α + Β) + 3·Α + Β)/((x + 1)·(x + 3))

{Α + Β = 4

{3·Α + Β = 0

risolvo: [Α = -2 ∧ Β = 6]

∫(4·x/(x^2 + 4·x + 3)) dx =

=6·LN(x + 3) - 2·LN(x + 1)

Valutato in x = 2:

6·LN(2 + 3) - 2·LN(2 + 1) = 2·LN(125/3)

Valutato in x = 0 :

6·LN(0 + 3) - 2·LN(0 + 1) = 6·LN(3)

Quindi:

2·LN(125/3) - 6·LN(3) = 2·LN(125/81)

 



1
IMG 4387



Risposta
SOS Matematica

4.6
SCARICA